HEMOSTATIC PARAMETER LEVELS AND DEMENTIA RISK IN THE CARDIOVASCULAR HEALTH STUDY. (11th November 2018) - Harrington, L; Ehlert, A; Jenny, N; Lopez, O; Cushman, M; Fitzpatrick, A; Mukamal, K; Jensen, M
Abstract: Background: Hemostasis is a key factor in cerebrovascular disease, but the association of individual hemostatic parameters with future risk of dementia is unclear. Objective: To prospectively evaluate associations between hemostatic parameter levels and dementia risk in the Cardiovascular Health Study (CHS). Methods: Eligible participants were older adults enrolled in the CHS Cognition Study, without dementia at baseline (1992/1993) who underwent measurement of platelet count, fibrinogen, factor VIIc [FVIIc], and factor XI [FXI]) (n=3, 185). Dementia was adjudicated through 1998/1999. We defined baseline mild cognitive impairment (MCI) by a score <88 on the Modified Mini-Mental State Examination. Cox models separately estimated hazard ratios and confidence intervals for dementia associated with 1-standard deviation (SD) increments in each hemostatic parameter, adjusting for sociodemographic and clinical risk factors and APOE genotype. Results: Dementia risk was not associated with platelet count (HR=1.01, 95% CI: 0.91, 1.13), fibrinogen (HR=1.07, 95% CI: 0.96, 1.18), FVIIc (HR=1.03, 95% CI: 0.92, 1.17), or FXI (HR=1.01, 95% CI: 0.91, 1.13) levels. There was no evidence of effect modification by APOE genotype and no consistent evidence of effect modification by baseline MCI. Conclusions: In this cohort of older adults, we found no evidence of an association between platelet count or levels of fibrinogen, FVIIc, or FXI and future dementia risk. While levels of these hemostatic parameters are associated with thrombotic event risk, unique brain physiology may not be reflected in levels of these biomarkers in blood.